Time-Lapse Electrical Resistivity Tomography Imaging of Buried Human Remains in Simulated Mass and Individual Graves - Doro, Kennedy O.; Emmanuel, Efemena D.; Adebayo, Moses B.; Bank, Carl-Georg; Wescott, Daniel J.; Mickleburgh, Hayley L. (Frontiers in Environmental Science, 2022)
Electrical resistivity has been used as a non-invasive geophysical technique for locating clandestine graves and monitoring human decay within the subsurface. Detailed studies assessing resistivity anomalies due to soil disturbances and decay products associated with graves have relied on the use of proxies such as pigs with limited studies using real human cadavers and simulating a mass grave setting and none assessing the anomalies in 3D. In this study, we used time-lapse 2D and quasi-3D electrical resistivity distribution measured over an experimental mass grave, and individual graves containing human cadavers to assess resistivity anomalies resulting from graves and the presence of decaying human remains in them. This study is part of a novel multidisciplinary mass grave experimental study with six graves consisting of a mass grave with six human cadavers, a controlled mass grave with none, three individual graves with one human cadaver each and a control individual grave with none. Nine parallel resistivity transects which allow us to image these graves in their 3D context were acquired prior to excavation and two days, one, two and six months after burial using a dipole-dipole electrode array, a unit electrode spacing of 0.5 m and an inter-profile spacing of 1 m. The value of different electrode arrays and spacings in identifying contrast between the graves was also assessed using forward models and field data. Soil sensors were installed at different locations in the graves to monitor the soil electrical conductivity, moisture content and temperature. Results of this study show an increase in electrical resistivity two days after burial in all graves with human remains as well as the control graves, which we attribute to increased soil aeration where disturbed pores are filled with air. The resistivity decreases thereafter in graves with human remains which we attribute to the formation of conductive leachate. This study validates the potential of electrical resistivity as a forensic search tool for locating both clandestine mass and individual graves and as a non-invasive monitoring technique to support human decomposition research.